Aubrieta alshehbazii (Brassicaceae), a new species from Central Turkey - Dönmez, Ali A.; Aydin, Zübeyde Uğurlu; Koch, Marcus (Phytotaxa, 2017)
Aubrieta alshehbazii is described as a new species that was collected from rocky steppe of Central Turkey. The new species is sympatric and most similar to A. pinardii , but differs by leaf shape, leaf margin, petiole, indumentum and inflorescence. A detailed morphological description, figures and comparisons with potentially closely allied species are provided herein. The new species is assigned to CR threat category of the IUCN. Beside this, due to further studies on type material of various Aubrieta taxa, A. anamasica is proposed as a new synonym of A. pinardii